Making Banana Heart Steak Vegetarian Food - Lumare, Mercy A.; Sinolungan, Linda; Umboh, Varen O. C. (Indo Consultan Energi, 2024)
Vegetarian steak dishes have had many changes or modifications from the general recipe. Steak food is made by modifying the ingredients and shape of the steak. Additionally, vegetarian steak has many recipe modifications in the current culinary era. As time passes, interest in vegetarian food starts to increase due to the increasing interest in the demands of a healthy lifestyle. The discovery of the idea of ​​modifying a vegetarian steak menu using typical Minahasan spices is a relatively new creativity in the culinary world. Therefore, it is prideful to elevate and preserve Minahasa culture through food. Activities to develop and introduce this food menu have been carried out in various ways, such as food tests for people who eat vegetarian and non-vegetarian food. Vegetarian food testing for banana flower steak was done using organoleptic tests at a well-known hotel restaurant. The results of testing this banana flower steak food have received official recognition. Therefore, vegetarian steak made from Minahasan spices is considered suitable for consumption and marketing.